PERLINDUNGAN SOSIAL BAGI ANAK BERHADAPAN DENGAN HUKUM DI KOTA PALEMBANG - Indah Huruswati (Sosio Konsepsia, 2009)
Implementation of Law Number 23 Year 2002 about the Protection for Children that guarantees to protect the children's rights (right of life, right to grow, protection and participation) has not been implemented particularly in children dealing with the law in investigation process. Likewise it is with a joint decision between the Minister of Justice of Indonesia, Indonesian Minister of Manpower and Ministn; of Social Affairs Number: Mo.1 -PK.03.01 Year 1984, No. KEP/HUK/X/19984 on cooperation in the implementation of Training Programs for Prisoners and Social Rehabilitation Re-socialization Janner state Prisoners and children; and an agreement between the Director General of Social and Rehabilitation Services, Department of Social Affairs and Director General of Penitentian; Department of Justice and Human RightsRI, apparently still not understood. Policy implementation should be able to guide even; decision of the judges which should give priority to the best interests of the child and the legal values that developed in the community. The basic ideas are exploitation, cruelty, violence, threats of violence, or abuse of children during the proceedings should be avoided. To obtain feedback on the implementation of the policies carried out by using the techniques of research focused discussions with officials from the agencies goals and obseniations related to prison for children at Prison Pa'jo, Palembang.